A Novel Control System for a Laptop with Gestures Recognition - Ramadan, Amira Fathy; Abd-Alsabour, Nadia (Journal of Trends in Computer Science and Smart Technology, 2024)
An important lesson learned during the pandemic is that the devices utilized by many people (vending machines, elevators, etc.) can spread the virus and take advantage of contactless programs that can be enabled through gesture recognition. It's a major enabler of smart living and human-computer interaction. It is widely used in controlling equipments. This research presents a novel vision-based real-time gesture recognition system for controlling a laptop. It's a comprehensive system that can do all the required functions needed to remotely control a laptop through hand gesture recognition rather than employing a mouse or keyboard. This system allows changing the position of the mouse point, performing left-click, right-click, double-click, and scrolling up and down. It also provides all the keyboard shortcuts, Print Screen (PrtScr), and Backspace. Furthermore, it allows shutting down as well as creating files and folders. Additionally, it allows playing, muting, pausing media playback, reducing/increasing the brightness, and turning the volume down/up. Moreover, it allows advancing to the next and previous page of the slideshow, as well as zooming in/out. Finally, the system allows gestures to open the most frequently used applications based on the user's choice. In comparison to the previous work, this system is considered unique in that it performs all the functions needed to remotely control the laptop. Previous systems only offer a subset of the tools provided by this proposed system Additionally, it is unique because the user operates all functions solely through gestures, without the need for additional methods.
Keywords: Human-Computer Interaction; Gesture Recognition; Computer Vision-Based Methods; Real-Time Hand Gestures Recognition; Static and Dynamic Hand Gestures Recognition